An innovative approach for planning and execution of pre-experimental runs for Design of Experiments - Muhammad Arsalan Farooq; Henriqueta Nóvoa; António Araújo; Sergio M.O. Tavares (European Research on Management and Business Economics (ERMBE), 2016)
This paper addresses the study of the pre-experimental planning phase of the Design of Experiments (DoE) in order to improve the final product quality. The pre-experimental planning phase includes a clear identification of the problem statement, selection of control factors and their respective levels and ranges. To improve production quality based on the DoE a new approach for the pre-experimental planning phase, called Non-Conformity Matrix (NCM), is presented. This article also addresses the key steps of the pre-experimental runs considering a consumer goods manufacturing process. Results of the application for an industrial case show thatthis methodology can support a clear definition ofthe problem and also a correct identification of the factor ranges in particular situations. The proposed new approach allows modeling the entire manufacturing system holistically and correctly defining the factor ranges and respective levels for a more effective application of DoE. This new approach can be a useful resource for both research and industrial practitioners who are dedicated to large DoE projects with unknown factor interactions, when the operational levels and ranges are not completely defined. – – El presente ensayo aborda el estudio de la fase pre-experimental de planificación del Dise\~no de Experimentos (DoE) con el fin de mejorar la calidad del producto final. En dicha fase pre-experimental de planificación se incluye una identificación clara del planteamiento del problema, de la selección de los factores de control y de sus correspondientes niveles y rangos. Para mejorar la calidad de producción basada en el DoE se presenta un nuevo enfoque para la fase pre-experimental de planificación llamado Matriz de No Conformidades (NCM). Este ensayo aborda también los pasos clave de las series experimentales teniendo en cuenta el proceso de fabricación de artículos de consumo. Los resultados de la puesta en marcha para un caso industrial demuestran que esta metodología puede respaldar una definición clara del problema y también la correcta identificación de los rangos de factores para situaciones concretas. Este nuevo enfoque propuesto permite modelar todo el sistema de fabricación de manera holística y definir correctamente los rangos de factores y niveles correspondientes para una puesta en marcha eficaz del DoE. Dicho enfoque puede ser un recurso útil tanto para profesionales de la investigación como de la industria que se dedican a grandes proyectos de DoE cuyas interacciones de factores son desconocidas, cuando los niveles y rangos operativos no están definidos del todo
Keywords: L66; 650; Pre-experimental runs; Non-Conformity Matrix; Design of Experiments; Series pre-experimentales; Matriz de no conformidades; Dise\~no de Experimentos